An Empirical Investigation of Viability of Alternative Approaches to Basic Education among the Samburu Nomadic Pastoralists Of Northern Kenya - Lanyasunya, Andrew Ropilo; Ogogo, Collins Omondi; Waweru, Samuel N. (Journal of Education and Practice, 2012)
Alternative Approaches to Basic Education (AABE) were introduced in Kenya to promote access to basic education and to enhance Universal Primary Education (UPE.) However, in Samburu County, the levels of school enrolment and literacy have been chronically low currently at 44% and 12% respectively. In order to investigate the success of AABE in Samburu County, this study tested government policy, resource-input, perception, nomadic pastoralists’ lifestyle, distance and AABE approaches applied in Samburu County. Primary data were collected using structured questionnaires for 400 learners’ household heads, 56 teachers from 56 AABE Centres and 10 AABE providers, while secondary data was obtained from the Ministry of Education offices, AABE Centres, libraries and the internet. Stratified random sampling technique was used, while descriptive and inferential statistics were employed to analyze and present the data. The study found that 92.5% of the population regarded AABE as inferior to formal education, 69.1% viewed government policy as lacking, 91.1% viewed AABE approaches as inappropriate, 80% acknowledged that nomadic lifestyle affected success of AABE, 62.7% indicated that AABE Centres were beyond the ideal 2.5 km and 73.4% said that resource input was inadequate. The study recommended for policies with a multi-faceted approach to development in nomadic pastoralist areas, addressing the problems of water, medical facilities, infrastructure, livelihoods and conflicts as a way of mitigating low enrolment and literacy levels.
Keywords: non-formal education; alternative education approaches; basic education; literacy; nomadic pastoralists.